The Effect Of Giving Boiled Chicken Eggs And Papaya Fruit On The Improvement Of Hemoglobin Levels In Anemia Students - Dewi Susanti; Faridah. Bd; Alsri Windra Doni; Yuli Amalia (Politeknik Kesehatan Kemenkes Jakarta II, 2019)
Anemia in adolescent girls is quite high, the incidence of anemia nationally is 21.7%. Anemia in adolescents if left untreated will continue into adulthood and contribute greatly to AKI, premature babies, and low birth weight babies. One way to prevent this can be done by consuming boiled chicken eggs and papaya fruit. The purpose of this study was to determine the effect of boiled chicken eggs and papaya fruit on increasing Hb levels in anemic female students of SMP Negeri 22 Kerinci in2019. This type of research was quasi experiment design of one group pretest posttest design with a sample of 16 respondents, purposive sampling sampling technique using the GCHB easy touch instrument and observation sheet. Univariate and bivariate data collection using paired t test. The results of the study average hemoglobin before treatment is 10.456 gr / dL and after treatment that is 12.412 gr / dL. Paired sample t test obtained the average difference before and after treatment was 1.9563 gr / dL with p value = 0,000 <0.05. It was concluded that there was an effect of giving boiled chicken eggs and papaya to an increase in hemoglobin levels in anemic female students. Suggestions that female Kerinci Junior High School 22 Kerinci teachers who experience mild anemia to invite their students to consume boiled chicken eggs and papaya fruit as an alternative in dealing with mild anemia experienced by students